Cold- and warm-temperature emissions assessment of n-butanol blends in a Euro 6 vehicle. (15th May 2018) - Lapuerta, Magín; Ramos, Ángel; Barba, Javier; Fernández-Rodríguez, David
Highlights: Euro 6 vehicle tested under driving cycle with n -butanol blends at 24 °C and −7 °C. Butanol blends up to 16% showed benefits in particle number and mass emissions. Benefits in engine efficiency were observed at cold ambient temperature (−7 °C). NOx increases found at cold temperature and CO and THC increases at any temperature. Butanol contents above 13% led to startability problems at cold ambient conditions. Abstract: Alcohols produced from waste or lignocellulosic materials with advanced production techniques constitute a sustainable alternative as diesel fuel component. With respect to ethanol, the higher heating value of n -butanol together with its better miscibility with diesel fuel and lower hydrophilic character suggest that butanol is a better option as blending component for diesel fuels. A Euro 6 Nissan Qashqai 1.5 dCi light-duty vehicle was tested following the NEDC (New European Driving Cycle) on a chassis dynamometer located in a climatic chamber with different blends of diesel and n -butanol. Room temperatures were set at 24 ° C and −7 ° C. Butanol blends up to 16% (volume basis) showed benefits in particle number and particulate matter emissions upstream of the DPF at any ambient condition, this implying a reduction in the frequency of regeneration. Benefits in engine efficiency were observed at cold ambient temperature (−7 ° C), just when the efficiency is poorest. Increases in NOx emissions were observed only at cold ambient temperature (−7 ° C), while increases in CO and hydrocarbon emissions were found at any temperature. Blends with n -butanol content above 13% led to startability problems at cold ambient conditions. In general, including n -butanol as a blend component is beneficial for both performance and particulate emissions, but the blend concentration is limited by startability problems at very low ambient temperature.